2019
DOI: 10.1136/bmjdrc-2019-000690
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain is not associated with serum vitamin D but is associated with female gender in patients with type 2 diabetes mellitus

Abstract: ObjectiveNeuropathic pain is a common complication of diabetes mellitus (DM). Patients may complain of several neuropathic symptoms including impaired peripheral sensation, numbness, tingling, burning, and pain. Because these symptoms may cross with symptoms of vitamin D deficiency, we hypothesized that neuropathic pain and vitamin D deficiency may be associated in patients with type 2 DM.Research design and methodsThis is a cross-sectional study that involved 239 participants with type 2 DM. Neuropathic pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
(66 reference statements)
0
11
1
2
Order By: Relevance
“…[2] [43] [80] [99] Obesity can also place joints under strain, and limit physical activity, which are potential explanations for its association with neuropathic pain found in rheumatoid arthritis. [42] Finally, poor health-related QoL also appears to be predictive of neuropathic pain, [3] as well as an outcome (as noted above).…”
Section: Social/lifestyle Risk Factorsmentioning
confidence: 82%
“…[2] [43] [80] [99] Obesity can also place joints under strain, and limit physical activity, which are potential explanations for its association with neuropathic pain found in rheumatoid arthritis. [42] Finally, poor health-related QoL also appears to be predictive of neuropathic pain, [3] as well as an outcome (as noted above).…”
Section: Social/lifestyle Risk Factorsmentioning
confidence: 82%
“…Some studies reported more severe neuropathy [ 20 , 21 , 23 ] and a higher prevalence of neuropathy in men than in women [ 20 25 ]. However, a higher prevalence in women than men has also been reported [ 26 ]; women also more often and more intensely experience neuropathic pain [ 23 , 27 ]. Additionally, some studies reported no sex difference in the prevalence of neuropathy [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a small amount of literature reported different results. For example, a cross-sectional study that involved 239 participants with T2DM revealed that neuropathic pain was not associated with serum vitamin D ( 58 ). Besides, a case-control study included 25 T2DM patients with DPN and 25 healthy controls reported that the severe form of neuropathy was more liable for lower vitamin D levels ( 59 ).…”
Section: Discussionmentioning
confidence: 99%